2024
DOI: 10.1108/arla-08-2023-0140
|View full text |Cite
|
Sign up to set email alerts
|

Firm-specific investor sentiment and earnings management: evidence from Brazil

Alexandre Esteves,
Pedro Piccoli

Abstract: PurposeThe purpose of this study is to investigate the influence of firm-specific investor sentiment on Brazilian companies’ accrual-based earnings management between 2010 and 2018. The paper aims to bring deeper insight into the relationship between the investor expectations and managers’ decision-making in an emerging market.Design/methodology/approachThe authors use the quantitative approach and apply a multiple linear regression model to test the relationship among the abnormal accruals, the firm-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Esteves and Piccoli (2024) study 175 companies operating in Brazil and found that optimistic/pessimistic (or neutral) investors’ expectations are negatively related to the earnings management through accruals. The authors use a quantitative approach and apply a multiple linear regression model to test the relationship among the abnormal accruals, the firm-specific investor sentiment index and the control variables.…”
mentioning
confidence: 99%
“…Esteves and Piccoli (2024) study 175 companies operating in Brazil and found that optimistic/pessimistic (or neutral) investors’ expectations are negatively related to the earnings management through accruals. The authors use a quantitative approach and apply a multiple linear regression model to test the relationship among the abnormal accruals, the firm-specific investor sentiment index and the control variables.…”
mentioning
confidence: 99%